Rapid shift in microbial community structure in a neutral hydrothermal hot spring from Costa Rica - Rojas Gätjens, Diego (2020)
In this work, we characterize the geochemistry and microbial community of Bajo las Peñas, a neutral (pH 6.5-7.4), hot spring (T = 62.0-68.0°C) located near Turrialba Volcano, Costa Rica. The microbiota at its two sources belongs mainly to the family Aquificae, comprising OTUs closely related to the genera Sulfurihydrogenibium, Thermosulfidibacter, Thermodesulfovibrio and Thermocrinis which is consistent with the presence of moderate levels of sulfate (243-284 mg/L) along the stream. We determined a dramatic shift in the microbial community just a few meters downstream of the sources of the hot spring (15-20 meters), with a change from sulfur related chemoautotrophic (e.g. Sulfurihydrogenibium and an OTU closely related to Thermodesulfovibrio) to chemoheterotrophic prokaryotes (e.g. Meiothermus, Nitrososphaera, Thermoflexus, Thermus). Thus, in this neutral hot spring, the first level of the trophic chain is associated with photosynthesis as well other anaerobic CO2 fixing bacteria. Then, thermotolerant chemoheterotrophic bacteria colonize the environment to degrade organic matter and use fermentative products from the first level of the trophic chain. Our data demonstrate how quickly the microbial community of an ecosystem can change in response to environmental variables and sheds light on the microbial ecology of less common circumneutral pH hot springs.